PENGEMBANGAN MEDIA INTERAKTIF BERBASIS WORDWALL TERHADAP HASIL BELAJAR IPA SISWA - Septianih, Nabilah; Nuraeni, Yeni; Nurfadhillah, Septi (Universitas Negeri Medan, 2024)
The science learning process plays an important role in actively involving students in the learning process. This can be facilitated by developing a Wordwall